Strasseriolides display in vitro and in vivo activity against trypanosomal parasites and cause morphological and size defects in Trypanosoma cruzi. - Cristina Bosch-Navarrete; Guiomar Pérez-Moreno; Frederick Annang; Rosario Diaz-Gonzalez; Raquel García-Hernández; Hedy Rocha; Francisco Gamarro; Carlos Cordón-Obras; Miguel Navarro; Ana Rodriguez; Olga Genilloud; Fernando Reyes; et al. (Public Library of Science (PLoS), 2023)
Neglected diseases caused by kinetoplastid parasites are a health burden in tropical and subtropical countries. The need to create safe and effective medicines to improve treatment remains a priority. Microbial natural products are a source of chemical diversity that provides a valuable approach for identifying new drug candidates. We recently reported the discovery and bioassay-guided isolation of a novel family of macrolides with antiplasmodial activity. The novel family of four potent antimalarial macrolides, strasseriolides A-D, was isolated from cultures of Strasseria geniculata CF-247251, a fungal strain obtained from plant tissues. In the present study, we analyze these strasseriolides for activity against kinetoplastid protozoan parasites, namely, Trypanosoma brucei brucei, Leishmania donovani and Trypanosoma cruzi. Compounds exhibited mostly low activities against T. b. brucei, yet notable growth inhibition and selectivity were observed for strasseriolides C and D in the clinically relevant intracellular T. cruzi and L. donovani amastigotes with EC50 values in the low micromolar range. Compound C is fast-acting and active against both intracellular and trypomastigote forms of T. cruzi. While cell cycle defects were not identified, prominent morphological changes were visualized by differential interference contrast microscopy and smaller and rounded parasites were visualized upon exposure to strasseriolide C. Moreover, compound C lowers parasitaemia in vivo in acute models of infection of Chagas disease. Hence, strasseriolide C is a novel natural product active against different forms of T. cruzi in vitro and in vivo. The study provides an avenue for blocking infection of new cells, a strategy that could additionally contribute to avoid treatment failure.